THE SCOPE OF THE CONTRA PROFERENTEM RULE IN THE INTERPRETATION OF THE GENERAL TERMS OF THE CONTRACT - Vukadinović, Slobodan (Pravni zapisi, 2020)
Having the rules of contract interpretation as a starting point, in this article the author considers two indisputable conditions for the application of the contra proferentem rule: (1) ambiguity of the provision, as an issue separate from the fact that the provision has become disputable among the contractors; and (2) the fact that the contract was unilaterally proposed or independently drafted by one contracting party. The article then focuses on the following contentious issues: (a) whether the contra proferentem rule is necessarily related to the protection of the weaker party or it is applicable regardless of the power disproportion between the contracting parties; (b) whether conducting negotiations and the existence of a reasonable possibility for the other party to become acquainted with the general conditions before the contract conclusion preclude the application of this rule; (c) whether the contra proferentem rule should be applied restrictively or extensively and without special conditions in contemporary law; and (d) whether this rule is a general and universal legal principle or applicable only when expressly provided by the relevant national legislation. If answers to these questions can be graded, then they could be taken into account proportionally when measuring the scope of application of the contra proferentem rule. In that situation, it could be asserted that the greater the scope, intensity, and effectiveness of the negotiations that preceded the contract conclusion, the less the justification for the application of this rule of interpretation, and vice versa. On the other hand, starting from the inequality of the parties, it can be asserted that the greater the inequality between the parties in terms of bargaining power, experience, genuine inequality, etc., the greater the need to apply this principle. The author emphasizes that the contra proferentem rule is used for the interpretation of adhesion contracts. Therefore, its scope should be determined in each particular case, taking into account the actual influence of the other party on the choice of provisions governing the contractual relationship, and bearing in mind that between general conditions and adhesion contracts a sign of equality does not necessarily exist. Consequently, it seems that not only exclusive but also proportional application in determining this rule’s scope in a specific situation is possible. The author also points out that the scope of its application may depend on the determination of the goal and value one protects, whereby the determination to protect the weaker party or to protect the conscientious and moral conduct of the party and the prohibition of abuse, can lead to different results. Accordingly, the author argues that although the contra proferentem rule is necessary to prevent potential abuses of the contracting party that independently creates the general conditions of the contract, this rule should not be abused by the other contracting party either. More precisely, it should not be used as ainstrument in situations when, during the contract implementation phase, it becomes evident that the fulfillment of the other party’s contract obligation has subsequently become difficult or costly. Respecting the postvention and preventative role it has, the contra proferentem rule is one of the subsidiary and special rules of interpretation. The rule is to be applied in compliance with general and other special rules of interpretation, primarily seeking the common intention of the parties. The application of the contra proferentem is conditioned and limited, and justified only when it is founded and appropriate. The extent of its scope in practice should depend on the circumstances of each particular case, while at the same time taking into account the basic principles of the contract law.